Evaluation of Soil Fertility Improvement Potential of Water and Methanolic Neem (Azadirachta indica A. Juss) Leaf Extract on the Growth and Yield of Tomato (Solanum lycopersicon L.) - A. O. Salami; O. O. Coker; O. O. Idowu (Archives of Current Research International, 2018)
An experiment was conducted during the period from May 2015 and August 2015 at Screenhouse of a faculty of Agriculture, Obafemi Awolowo University, Ile-Ife, Nigeria to evaluate the fertility content of different extracts of neem on growth and yield of tomato. The experiment consisted of methanolic extract of neem in sterilized soil with tomato plant, methanolic extract of neem in unsterilized soil with tomato plant, water extract of neem in sterilized soil with tomato plant, water extract of neem in unsterilized soil with tomato plant and the two controls which are sterilized soil with tomato plant and unsterilized soil with tomato plant. Treatments were in triplicate and arranged in a randomised complete block design (RCBD). Regarding yield, treatment with methanolic neem in sterilised soil had 8 fruits during the 4 weeks of harvest while the least number of fruit was in treatment with water extract of neem in the unsterilised soil which had 1 fruits all through. The highest value for the weight of fruit was also recorded in treatment with methanolic neem in sterilised soil with the mean of 0.8 gram while the treatment with methanolic neem extract in unsterilised soil had the least value of 0.2 gram which was lower than the two controls. The diameter of fruit showed that the treatment with methanolic neem extract in sterilised soil had the highest value with the mean of 25.43 cm while the minimum value for diameter was recorded in treatment with methanolic neem extract in unsterilized soil with mean of 6.54 cm. Regarding growth, results at Nine weeks after planting showed that someof leaves, leaf area and vine length was significantly higher in treatment with neem methanolic extract in the sterilised soil, while girth size and a number of branches were higher in the control treatment with decontaminated soil. It is recommended that methanolic neem extract should be used by farmers to increase tomato production.